2005
DOI: 10.1182/blood-2004-03-1208
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antilymphoma efficacy of CD19-redirected influenza MP1–specific CTLs by cotransfer of T cells modified to present influenza MP1

Abstract: IntroductionAdoptive transfer of ex vivo-expanded T cells specific for immunodominant viral epitopes into immunocompromised hosts can reconstitute protective antiviral immunity and can result in the long-term persistence of transferred cells. [1][2][3][4][5] In contrast, the application of adoptive T-cell transfer to the successful cellular immunotherapy of malignancy has proved to be significantly more challenging, in part because of the difficulty of isolating high-affinity, tumor-specific T cells that can m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 47 publications
1
97
1
Order By: Relevance
“…Immunogens used to date are alloantigen 8 in mouse cells, and Epstein-Barr (virus) EBV 27 and cytomegalovirus (CMV) 28 and influenza virus 29 in human cells. Importantly, the potential utility of dual-specific T cells was highlighted by the demonstration of tumor inhibition in mice using mouse dual-specific T cells recognizing alloantigen and the ovarian cancerassociated antigen FBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunogens used to date are alloantigen 8 in mouse cells, and Epstein-Barr (virus) EBV 27 and cytomegalovirus (CMV) 28 and influenza virus 29 in human cells. Importantly, the potential utility of dual-specific T cells was highlighted by the demonstration of tumor inhibition in mice using mouse dual-specific T cells recognizing alloantigen and the ovarian cancerassociated antigen FBP.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of generating and transducing influenza-specific human T cells has been previously demonstrated. 29 Alternatively, an attenuated virus may be suitable, or a widespread persistent virus such as EBV or CMV may be an effective second specificity to use. The possibility of generating human dual-specific T cells with reactivity against tumor and EBV or CMV has been previously demonstrated in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…For example, to increase the proliferative potential (i) the CAR endodomain can be systematically altered to provide a fully competent activation signal, [105][106][107][108][109][110][111] or (ii) T cells can be modified to enforce expression of stimulatory cytokine transgenes [112][113][114][115][116] or (iii) the CAR can be introduced into T cells which can respond/ proliferate via endogenous TCR to defined (often viral) antigens. [117][118][119] Recognizing that tumor-specific T cells may not traffic to sites of disease, cells can be genetically modified to express desired homing receptors. 120 Gene transfer can also be undertaken to render T cells resistant to the anti-inflammatory tumor micro-environment, such as by expressing a dominant-negative TGF-b receptor 121,122 or decreasing the sensitivity of the adoptively-transferred T cells to Fas-induced apoptosis.…”
Section: Adoptive Cellular Immunotherapy Using Genetically Modified Tmentioning
confidence: 99%
“…[28][29][30][31][32][33] As an alternative source of APC, investigators have also used T cells, which can be nonspecifically propagated ex vivo to vast numbers by cross-linking CD3 with OKT3, as a source of antigen present cells (T-APC). [34][35][36][37] (iv) The safe and efficacious infusions of EBV-specific T cells for LPD has facilitated the targeting of other EBV-derived antigens associated with Hodgkin's disease (HD), and nasopharyngeal carcinoma (type II EBV malignancies) with investigators developing technologies to generate T cells with specificity for latency membrane protein (LMP) 1, LMP2 and EBNA-1. 38-46 (v) Since the generation of EBV-specific T cells on LCL requires weeks of cell-culture time, investigators have recently developed a paradigm for the a priori manufacture of HLA-restricted EBV-specific T cells.…”
Section: Adoptive Cellular Immunotherapy For Ebvmentioning
confidence: 99%
“…[25][26][27][28][29] The initial construct was composed of a CD19-specific single-chain immunoglobulin extracellular targeting domain, fused to a CD3-zeta intracellular signaling domain. It was shown that CD19-redirected CTL were capable of potently killing primary B-ALL blasts and also of producing Th1 cytokines and were consistently proliferating after recognition of the targeted molecule.…”
Section: Applications Of Chtcr In the Context Of Hematologic Malignanmentioning
confidence: 99%